Identification of Differentially Expressed Biomarkers in Neoplasm Colorectal Cancer (Eurasian Medical Research Periodical, 2022)
Colorectal cancer is the third most common cancer worldwide, in which cells in the colon or rectum grow out of control. There are estimated 1.93 million colorectal cancer cases and 0.94 million deaths due to colorectal cancer. The aim of this study was to identify differentially expressed genes (DEGs) and associated biological processes between colorectal neoplasm and adjacent normal tissues using a high-throughput bioinformatics approach to elucidate their potential pathogenesis. The raw reads of gene expression profiles of the E-MTAB-8448 dataset, originally produced through use of the high-throughput RNA sequencing technique, were downloaded from the ArrayExpress database, excluding cell-cultured samples. The E-MTAB-8448 dataset contains information from 124 samples, including 58 normal samples and 66 neoplasm samples. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes pathway (KEGG) enrichment analyses were performed to identify functional categories and associated molecular and biochemical pathways, respectively, for the identified DEGs. GO and KEGG results suggested that several biological pathways PI3K-Akt signaling pathway, MAPK signaling pathway, JAK-STAT signaling are commonly involved in the development of various cancers including colorectal cancer. This study provides further insights into the underlying pathogenesis of colorectal cancer through identification of key biomarkers, which may facilitate the diagnosis and treatment of these diseases.